FOOD SAFETY REVIEWED FROM THE QUALITY OF MICROBA ON PORK SATAY IN THE TOURISM AREA SANUR DENPASAR CITY - ade jihan maeda bleszynsky; Ni Putu Agustini; Anak Agung Nanak Antarini (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2020)
Pork satay is a traditional Balinese food that is more in demand by local tourists or more in need of security assistance. The purpose of this study was to study the safety of pork satay in terms of microbial quality and food safety scores sold in the Sanur Beach area of Denpasar City. The type of research used is observative and uses microbial quantitative analysis. The research method used is the TPC test. TPC testing is to find out the total number of microbes contained in a product. Based on microbial test results from the number of samples obtained there were no samples that exceeded the total microbial limit of 1 x 104 CFU/g. based on coliform test in pork satay sample samples found 2 samples containing coliform exceeding 3 CFU/g but no contamination of pathogenic bacteria such as E. coli, Salmonella sp, Shigella sp and Vibrio cholera. Based on the food safety score (SKP) from the sample sample shows that the food safety score is still in the vulnerable range, but it is still safe to consume. Total microbes and bacterial contaminants show that food is still safe for consumption.